A combined use of embedded and cohesive elements to model damage development in fibrous composites. (1st September 2019) - Liu, Qiang; Gorbatikh, Larissa; Lomov, Stepan V.
Abstract: In recent years the embedded element (EE) technique, which is based on the superposition of meshes, has been introduced into finite element (FE) modelling of composite materials. When compared to conventional approaches employing a single continuous mesh this technique has a number of advantages, among which are simplicity in the model creation and improved mesh quality. However, due to the absence of physical interfaces, simulation of interfacial damage with this technique presents a real challenge. In this work we propose an approach in which the EE technique is combined with the cohesive zone model with the purpose to model interfacial damage in fibrous composites. The new hybrid method is validated against conventional FE models in four case studies. Among others the methodology is applied to predict mechanical properties of nanocomposites reinforced by carbon nanotubes showing good agreement with experimental data.